Relación entre las actividades antropogénicas y la calidad de agua del río carrizal, sitio El Limón, utilizando bivalvos como bioindicadores - Chancay García, Ramón Antonio (2019)
The purpose of this research was to evaluate the relationship between anthropogenic activities and the water quality of the Carrizal River, El Limón site, anthropogenic activities were determined through routes recorded on an observation sheet, subsistence agriculture predominates with a 50 % highlighting large-scale banana crops, livestock by 13% and tourism activities with 19%; three sampling stations were established (Puente El Morro, Puente El Limón, Lindero del Coliseo ESPAM); For the collection and sampling of bivalves, a Surber-type network was used during daylight hours; after the collection, the Shannon-Wienner index was applied, which was 2.98, which is considered a high average diversity; since four species were identified: Corbicula fluminea with 322 individuals, Larkinia grandis with 4 ind., Illichione subrugosa with 6 ind., and Crassostrea gigas with 12 ind., for the calculation of the Biotic Integrity Index (IBI) which produced a value of 24 which indicates a poor water quality, which rejected the idea to defend raised in the investigation and based on these results a survey was conducted that determined the degree of knowledge about pollution in the area and based to the opinions of the respondents, control and mitigation measures focused on river bed cleaning, riverbank reforestation, separation of solid waste and prohibition of liquid discharges into river water were developed.